Modern approaches to vestibular schwannomas treatment in patients with neurofibromatosis type 2 using stereotactic radiosurgery - Zemskova, Oksana; Chuvashova, Olga (Ukrainian Neurosurgical Journal, 2014)
Introduction. The results and efficacy of stereotactic radiosurgery (SRS) in treatment of patients with vestibular shwannomas (VS) associated with neurofibromatosis type 2 (NF2) are analyzed. Materials and methods. In 12 patients with NF2 (in total 17 VS) 15 VS-NF2 were irradiated using linear accelerator Trilogy. The prescribed doze (PD) for VS-NF2 was 12.0 – 13.0 Gy (median 12.5 Gy, in average 12.5 Gy); maximal doze — from 13.01 to 15.0 Gy (median 14.31 Gy, in average 14.19 Gy); targets volume — from 0.226 to 8.258 cm3 (median 3.564 cm3, in average 3.61 cm3). Results. In 15 VS-NF2, treated with SRS, local control was achieved in 93%. In 7 patients after SRS there were no negative changes in neurological state, in 4 of them positive clinical dynamics was observed. Hearing preservation rate was 57%. After SRS occlusive hydrocephalus, resistant trigeminal pain, aggravation of facial nerve dysfunction were not identified. Conclusions. SRS is non-invasive method of VS-NF2 treatment, it provides local control and preservation of cranial nerves function adjacent to the tumor.